Challenging the secret government : the post-Watergate investigations of the CIA and FBI - Olmsted, Kathryn S. (University of North Carolina Press, 1996)
A former U.S. trade official provides a critique of U.S. trade policies over the last 60 years, placing them within full historical perspective. (Please see cloth edition published 9/95.).